Sculpturscape '73 : an exhibitiion in Mildura, Australia. (Mildura : Mildura Arts Centre, 1973)
Allen, William Robert ; Andersson, J. Anders ; Angwin, Robin ; Armstrong, John ; Barber, Bruce Alistair ; Beadle, Paul ; Bishop, Tony ; Boyce, Donald ; Brecknock, Richard ; Brett, Graeme John ; Broughton, Owen ; Brown, Robert ; Bullmore, Edward ; Burns, Tim ; Carney, Chris ; Clark, Marc ; Clements, William ; Cole, Peter ; Coleing, Tony ; etc.
Sculpturscape '73, Mildura Arts Centre, Mildura, 7th April until 7th July 1973
boek